2011
DOI: 10.4236/psych.2011.26084
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Disruptive Behaviour and School Performance across Comprehensive School: A Prospective Cohort Study

Abstract: In the present study we examined 1) whether childhood disruptive behaviour, in terms of aggressiveness, hyperactivity and social adjustment, predicts school performance since toddler age or whether becomes it relevant first since middle or late childhood, 2) whether gender differences within the associations between school performance and disruptive behaviour exist, and 3) whether there are trait specific effects in these associations, i.e. whether hyperactivity is more relevant determinant for later school su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
1
6
0
1
Order By: Relevance
“…Sedentary behavior has also been shown to contribute to morbidity and mortality [45]. Research shows that high temperamental activity is associated with poor school performance in adolescent girls [46] and adult atherosclerosis in women [21]. High levels of temperamental activity are also shown to be related to ADHD [47].…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary behavior has also been shown to contribute to morbidity and mortality [45]. Research shows that high temperamental activity is associated with poor school performance in adolescent girls [46] and adult atherosclerosis in women [21]. High levels of temperamental activity are also shown to be related to ADHD [47].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors that influence the process of early school leaving are already identified [ 8 ] and can be divided in student-related (e.g. overall poor health in childhood and adolescence [ 3 ], externalizing and internalizing behavior [ 9 , 10 ], life-style, personality [ 3 , 11 , 12 ], sex differences and gender beliefs [ 13 ], family-related (e.g. living in a single-parent family[ 14 ]) and school-related factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the demonstrated impact of mental health problems on social, emotional, cognitive, and educational functioning, it is of critical importance that we bring our resources to bear on the reconceptualization of mental health care for the children and youth of Canada. The connection between mental health and school success (defined here as the number of years of education completed) has been established and examined; most recently researchers such as Alatupa and colleagues (2011) observed, in a longitudinal study of 973 youth over a 10-year span, that early disruptive behavior has long-lasting effects on grades. Depression has been linked with poor text comprehension and memory (Becker, Ellis, Varner, & Moore, 1997; Owens et al, 2012), and research has demonstrated a high rate of co-occurrence between learning disabilities, depression, and anxiety (see, for example, Canadian Council on Learning, 2009).…”
Section: Services For Children’s Mental Healthmentioning
confidence: 99%